2021
DOI: 10.3390/nu13114049
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Perioperative Nutrition Therapy for Patients Undergoing Pancreaticoduodenectomy: A Systematic Review with a Component Network Meta-Analysis

Abstract: Numerous strategies for perioperative nutrition therapy for patients undergoing pancreaticoduodenectomy (PD) have been proposed. This systematic review aimed to summarize the current relevant published randomized controlled trials (RCTs) evaluating different nutritional interventions via a traditional network meta-analysis (NMA) and component network meta-analysis (cNMA). EMBASE, MEDLINE, the Cochrane Library, and ClinicalTrials.gov were searched to identify the RCTs. The evaluated nutritional interventions co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…Tian et al 67 reported that postoperative administration in patients with esophageal cancer is associated with better control of infectious complications and postoperative pneumonia. In a meta-analysis of patients who underwent pancreaticoduodenectomy, Wang et al 68 reported that combined preoperative and postoperative administration was most effective. Pancreaticoduodenectomy is one of the most invasive surgical procedures, and the effect of timing of administration may vary with surgical invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al 67 reported that postoperative administration in patients with esophageal cancer is associated with better control of infectious complications and postoperative pneumonia. In a meta-analysis of patients who underwent pancreaticoduodenectomy, Wang et al 68 reported that combined preoperative and postoperative administration was most effective. Pancreaticoduodenectomy is one of the most invasive surgical procedures, and the effect of timing of administration may vary with surgical invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Across the 34 included papers, 26 included a network diagram [3, 11-13, 17-21, 23-27, 29-31, 33-36, 38-40, 42, 43], 17 included a summary forest plot at either the component or intervention level [1,3,9,12,13,20,21,23,27,28,30,32,33,[37][38][39]41] and 16 included other plots [1, 3, 12, 17, 20, 22, 23, 25-28, 34, 37-40] (Table 1). One paper included no plots [8].…”
Section: Review Of Visualisations Identified (With Discussion)mentioning
confidence: 99%
“…Wang et al провели обзор исследований для оценки различных способов питания пациентов после ПДР. Установлено, что наиболее благоприятный вариант для профилактики инфекционных осложнений и улучшения клинической картины заключается в использовании перорального питания иммунонутриентами [59].…”
Section: питание пациентов в послеоперационном периодеunclassified